Persepsi Masyarakat Terhadap Komunitas Anak Punk Di Kota Pekalongan - Fitri Awan Arif Firmansyah; Amelia Putri Nirmala (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2021)
This study aims to determine the perception of society towards the behavior of punk children in Pekalongan City. This research including field research that is qualitative. Sources of data in this study were taken from the data primary or basic data taken and obtained from field research through observation, interviews, documentation and population of five people in Pekalongan City, while secondary data is complementary data which obtained from documentation related to the problems in this research. Results This study shows that the public's perception of the behavior of punk children is considered trash society because they have negative attitudes and behaviors. What factors led to the existence of punk children? are family economic pressures, prohibitions from parents, want freedom, lazy personality. Keywords: Public perception, punk children, Pekalongan